Implementation of Integrated Social Welfare Services and Caring Society Movement to Prosperous District or City - Udiati, Trilaksmi; Murtiwidayanti, Sri Yuni (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study is aimed to identify and to describe the implementation of integrated social welfare services and caring society movement to district or city prosperous (Pandu Gempita). The research was conducted in Berau, East Kalimantan Province. The research data sources were gained from the managers of integrated services, regional authorized personnel working unit (SKPD), businesses, social organizations linked to poverty handling as many as 20 informants. Data collecting techniques were interview, observation and document studies. The data was analyzed in qualitative descriptive technique. The results showed that the implementation of UPTD-PTKS in Berau district was supported by related SKPD, by businesses, by society and by that of regional leaders’ commitment through local government budget support. Some obstacles appeared in the processes of personnel placement legal aspects for those managed the UPTD-PTKS so that the service still remained as a reference which can not be solved in UPTD-PTKS. There haven’t been Standard Operational Procedures (SOP) yet that regulate the work mechanism of SKPD concerned. There haven’t been Internet network and integrated database so that the target, concerned SKPD programs haven’t been unified to UPTD-PTKS as online, on the other hand UPTD-PTKS hasn’t functioned online yet to distribute services to SKPD concerned as needed by clients. It is then recommended to the Ministry of Social Affairs: revising the General Guidelines and Technical Guidelines on the position of Pandu Gempita (UPTD-PTKS), up grading the managing human resources and that of Pandu Gempita service implementation companions.